Asas Keadilan Dalam Kewenangan Peradilan Umum Dan Peradilan Militer Dalam Perkara Koneksitas Dalam Sistem Ketatanegaraan Indonesia - Marisa Oktora; Rina Antasari; Muhamad Sadi Is (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda Palembang, 2024)
Conflict cases are cases that involve civilian and military elements simultaneously, which raises jurisdictional issues between general courts and military courts. Military courts are often perceived as closed institutions, which triggers public doubts about transparency and justice in the law enforcement process against soldiers. In addition, there is an assumption that military court decisions tend to impose lenient sanctions. Based on the Criminal Procedure Code (KUHAP), the determination of jurisdiction in koneksitas cases is made through joint research between the (civilian) prosecutor and the military prosecutor. If the impact of the criminal act is more detrimental to the public interest, the case is tried in the general court; conversely, if it is more detrimental to the military interest, it is tried in the military court. However, changes in military criminal procedure law in Indonesia still do not fully address the needs of the general court, especially in the investigation process of TNI soldiers suspected of committing general crimes